Editorial Note - Mirnada, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Science faces unprecedented challenges, such as responding to the demand for food for population growth (2 billion more people by 2050), a broad and complex deck of problems where horticultural sciences focus on preserving the natural systems that sustain us, by avoiding the expansion of the agricultural frontier and desertification, improving food quality, minimizing pollution, preserving biodiversity, obtaining emissions-neutral and energy efficient agri-food systems, adapting to climate change, such as that go beyond the capacity of researchers/funders and require the participation of society in general.